1983
DOI: 10.1099/00222615-16-4-497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of glucose broth with nutrient broth blood cultures for the detection of "Streptococcus viridans" bacteraemia

Abstract: SUMMARY. Viridans streptococci were isolated from the blood stream of half of 50 patients undergoing dental extractions approx. 2 min before blood culture.Glucose and nutrient broths were tested in parallel. There was no significant difference between the isolation rates of streptococci by the two methods after incubation for 7 days, nor did the addition of glucose 0.1% to nutrient broth significantly increase the speed of detection of streptococci; the isolation rates of streptococci during the first 48 h of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Many studies have reported a frequency of postextraction bacteremia in children as significantly lower than the figures reported for adults. [ 5 6 ] In 2009, Lockhart et al ,[ 5 ] using a logistic regression model, found that the prevalence of bacteremia following dental extractions increased significantly with age. In contrast to these studies, we found that at all periods, the prevalence of the bacteremia was higher in lower age group than higher age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported a frequency of postextraction bacteremia in children as significantly lower than the figures reported for adults. [ 5 6 ] In 2009, Lockhart et al ,[ 5 ] using a logistic regression model, found that the prevalence of bacteremia following dental extractions increased significantly with age. In contrast to these studies, we found that at all periods, the prevalence of the bacteremia was higher in lower age group than higher age group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] Various studies have been conducted to study the association of bacteremia with dental procedures and to establish any correlation with factors like age, gender, type of procedure, duration of surgery, etc. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%